Engineered a dual-targeting biomimetic nanomedicine for pancreatic cancer chemoimmunotherapy - Meng Wang; Qida Hu; Junmin Huang; Xinyu Zhao; Shiyi Shao; Fu Zhang; Zhuo Yao; Yuan Ping; Tingbo Liang (Journal of Nanobiotechnology)
Abstract The therapeutic effect of chemotherapeutics such as gemcitabine against pancreatic cancer is considerably attenuated by immune-suppressive tumor microenvironment. Improvement of chemotherapeutic efficacy by targeting tumor-associated macrophage and reprograming tumor microenvironment to enhance their efficacy may become a promising strategy. To this end, we developed a biomimetic dual-targeting nanomedicine (PG@KMCM) where gemcitabine-loaded poly (lactic-co-glycolic acid) (PLGA) nanoparticles are coated with a layer of bioengineered cancer cell membrane that stably expresses peptides targeting M2-like macrophages (M2pep) while reserving tumor-associated antigens (TAAs). The PG@KMCM nanomedicine enables the simultaneous targeted delivery of gemcitabine to pancreatic tumor sites and TAMs to potentiate its therapeutic effects. Furthermore, the combination of an immune checkpoint inhibitor (PD-L1 antibody) with PG@KMCM synergistically enhanced the anti-tumoral effect by reprogramming the immune-suppressive tumor microenvironment, including the elimination of PD-L1-positive macrophages and the downregulation of PD-L1 expression. Our study proved dual-targeting PG@KMCM nanomedicine in combination with PD-L1 immune checkpoint inhibitor therapy is able to effectively reprogram the tumor microenvironment and kill pancreatic cancer cells to enhance overall therapeutic potential. Graphical Abstract